2022
DOI: 10.1002/uog.24750
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome after in‐vitro fertilization/intracytoplasmic sperm injection in women with congenital uterus didelphys

Abstract: Objective To investigate the pregnancy and obstetric outcomes of patients with congenital uterus didelphys who achieved clinical pregnancy after in‐vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI). Methods This was a retrospective matched‐cohort study of 83 infertile patients with uterus didelphys who underwent IVF/ICSI and achieved clinical pregnancy from January 2005 to December 2018 at our center. For each patient in the study group, three control patients with normal uterine morphology who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…For infertile couples, the relationship between vaccination and outcome of assisted reproductive technology remains unclear. Several studies ( 16 , 18 , 35 , 43 , 44 ) have reported that preconception COVID-19 vaccinations had no detrimental effect on either laboratory outcomes or short pregnancy outcomes after IVF/ICSI. However, Shi et al ( 16 ) reported that vaccinated women had a significant lower rate of clinical pregnancy with fresh embryo transfer.…”
Section: Discussionmentioning
confidence: 99%
“…For infertile couples, the relationship between vaccination and outcome of assisted reproductive technology remains unclear. Several studies ( 16 , 18 , 35 , 43 , 44 ) have reported that preconception COVID-19 vaccinations had no detrimental effect on either laboratory outcomes or short pregnancy outcomes after IVF/ICSI. However, Shi et al ( 16 ) reported that vaccinated women had a significant lower rate of clinical pregnancy with fresh embryo transfer.…”
Section: Discussionmentioning
confidence: 99%
“…From these, 6461 were screened by title and 328 by title and abstract. A final subset of 78 studies were full-text evaluated (Figure 1), of which 32 (Ban-Frangez et al, 2009;Ben-Rafael et al, 1991;Cahen-Peretz et al, 2017;Cai et al, 2021;Cooney et al, 1998;Crane et al, 2012;Chen et al, 2018;Chen et al, 2019;Erez et al, 2007;Hiersch et al, 2016;Hua et al, 2011;Jayaprakasan et al, 2011;Kong et al, 2021;Leible et al, 1998;Li et al, 2017;Lu et al, 2021;Marianna et al, 2022;Mastrolia et al, 2017;Mastrolia et al, 2018;Ouyang et al, 2020;Ozgur et al, 2017;Pleş et al, 2018;Prior et al, 2018;Qiu et al, 2022;Saravelos et al, 2010;Sugiura-Ogasawara et al, 2010;Surrey et al, 2018;Takami et al, 2014;Tomaževič et al, 2010;Zambrotta et al, 2021;Zlopasa et al, 2007) fulfilled inclusion criteria (Table SI). Scores granted by Newcastle-Ottawa Score and quality assessment using AHRQ standards are presented in Appendix 2.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Twelve of the studies selected by Kim et al (2021) were not included in our meta-analysis: one was published out of time limits (Forde et al, 1978) while the other eleven did not achieve the minimum score on the AHRQ-adapted NOS scale (Acién, 1993;Fox et al, 2014;Liang and Hu, 2010;Maneschi et al, 1995;Neal et al, 2019;Ravasia et al, 1999;Shuiqing et al, 2002;Sorensen and Trauelsen, 1987;Woelfer et al, 2001;Zhang et al, 2010;Zupi et al, 1996). Our meta-analysis includes seven studies not considered by Kim et al (2021) (Cai et al, 2021;Crane et al, 2012;Chen et al, 2018;Lu et al, 2021;Marianna et al, 2022;Qiu et al, 2022;Surrey et al, 2018).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Previous studies analyzed different malformations all together [ 6 ], while the results were skewed by the high proportion of arcuate uterus (e.g., 89.1% and 89.5%), which was once thought to be a minor defect that did not have any effect on pregnancy outcomes. Most studies have focused on only a particular type of uterine anomaly [ 7 9 ]. A retrospective study did rigorous work, but they focused solely on the frozen thawed embryo transfer (FET) outcomes of uterine anomaly [ 10 ], while the systematic study of fresh embryo transfer (IVF-ET) outcomes has not been studied.…”
Section: Introductionmentioning
confidence: 99%